Job's journey: stations of suffering - Oeming, Manfred; Schmid, Konrad (Critical studies in the Hebrew Bible, 2015)
"From the Introduction: "The book of Job does not promote silence about God because we cannot say anything about him. Otherwise, this book would never have been written. But the book of Job does bid farewell to certain types of theology--and we need not bemoan their loss: theology as the wisdom of the world projected into heaven; theology as pious reflection on a higher being that then mistakes traditional or innovative ideas about God entirely for God himself; theology that purports to communicate direct revelation from God. The book of Job distrusts and disbelieves all this to its core. Instead, it states clearly that this is not God; these are only graven images. Such fundamental criticism of all pseudo-theology is--and here we can only agree with the book of Job--not the end but the very beginning of theology." This book is not an attempt to cover every angle and answer every question that we have about the book of Job. Instead, Konrad Schmid, in the introductory chapter, provides us with an analysis of the structure of the book that helps us to see the book as a whole. And Manfred Oeming, in the chapters that follow, provides clear snapshots of various elements of the book, including a summary of the dialogues, Job's monologue, Elihu's speech ("the Anti-Monologue"), Job's encounter with God, and the destination (of Job's journey). Between them, the two authors provide an accessible scholarly and theological approach to the book that is richly satisfying"--
Includes bibliographical references and indexes
Keywords: Bible -- Criticism, interpretation, etc -- Bible -- Criticism, interpretation, etc; Bible -- Job -- Criticism, interpretation, etc